State aids, taxation and the energy sector - Aragón Gómez, Cristina (Colección de libros electrónicos de ULoyola, 2017)
EU State aids, taxation and the energy sector are matters of great importance in today?s globalised word that traditionally has been widely studied in an isolated way. This timely book fills the gap in the literature on EU State aids providing a set of twenty-three contributions from leading experts and scholars on key legal issues which appear when these tree topics are analysed with an integrated approach. Tue contributions included in this book addressed not only the current situation of the tax regulation on the energy sector and its relation with the State aid rules but also an analysis of the need of reform and the international framework can be found in its pages. Comparative law, competitive aspects, WTO implications and the environmental regulations and needs have been key issues for the elaboration of the book and the program of the international congress which has given place to it.